2003
DOI: 10.1088/0954-898x_14_2_303
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of cuneothalamic projection neurons

Abstract: The dorsal column nuclei, cuneatus and gracilis, play a fundamental role in the processing and integration of somesthetic ascending information. Intracellular and patch-clamp recordings obtained in cat in vivo have shown that cuneothalamic projection neurons present two modes of activity: oscillatory and tonic (Canedo et al 1998 Neuroscience 84 603-17). The former is the basis of generating, in sleep and anaesthetized states, slow, delta and spindle rhythms under the control of the cerebral cortex (Mariño et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The mathematical form for the T-type current has usually been chosen to be the linear expression (Destexhe et al, , 1996Rybak et al, 1997;Amini et al, 1999;Sanchez et al, 2003),…”
Section: Mathematical Expressions For I Tmentioning
confidence: 99%
“…The mathematical form for the T-type current has usually been chosen to be the linear expression (Destexhe et al, , 1996Rybak et al, 1997;Amini et al, 1999;Sanchez et al, 2003),…”
Section: Mathematical Expressions For I Tmentioning
confidence: 99%
“…This spatial arrangement is generated through somatotopically organized afferent organization consisting of direct excitatory input on CL cells and GAB mediated inhibition from surrounding areas [7]. It has been demonstrated that when this circuit is constructed with realistic models of cuneate cells [16], it can perform edge detection as well as motion discrimination [15].…”
Section: Introductionmentioning
confidence: 99%